Skills and Attitudes of Students which Affect Fostering of Critical Thinking in Undergraduate Medical Students - Muqeem, Ahmad; Arshad, Syma; Sajid, Sadaf; Ahmad, Abdullah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To identify students’ skills and attitudes which affect fostering critical thinking in undergraduate medical students. Study Design: Modified Delphi Study. Place and Duration of Study: University of Lahore, Lahore Pakistan, from Oct 2018 to Apr 2019. Methodology: This study was carried out to develop consensus. Participants were selected through purposive sampling. A draft questionnaire was developed on Google Forms and sent to five experts for pilot study, construct validation and cognitive pre-testing. Wait Time, rating on the Likert Scale and Consensus criteria of 80% were defined before the start of the study. A new questionnaire was sent to participants in each round. Results: The study enrolled 27 experts, of which only 14 participated in all the three rounds. Experts initially identified 18 factors related to students’ skills and attitudes. The consensus was achieved for 14 out of the final 16 factors. Pre-medical education through Matric/FSc. rote memorization, lack of logical and rational thinking, no active participation in interactive sessions and strategic learning by students hamper fostering critical thinking. On the other hand, students from O/A level possess better critical thinking skills because they were trained to criticize and question during class activities. Conclusion: Individual skills/attitudes of students affect fostering of critical thinking among undergraduate medical students. They should be addressed primarily in pre-medical schools for better critical thinking abilities in medical school.